Subjective Well-being and Intergenerational Support Exchange in Old Age in Rural Vietnam - Nguyen Ha Dong (Wieś i Rolnictwo)
This paper investigates how intergeneration support influence rural elders’ subjective wellbeing in Vietnam, based on the data of the survey ‘Strengthening Social En gagement in Elderly Care in Changing Economic and Family Structure in Asia: Policy and Practical Dialogues between Local Communities in Vietnam and Japan’ conducted in 2017. The sample analysis of this paper is 307 respondents aged 60 and older in rural areas in the middle of Vietnam. Subjective wellbeing includes psychological well-being, self-rated health and life satisfaction. We find that all elders’ psychological wellbeing becomes more positive when they provide financial support for their children. Despite the economic difficulties and the prevalence of filial norm, the financial provision is not viewed as the burden to the older adults but helps them to confirm their position and power in the intergenerational relations. Nonetheless, receiving the spiritual care is more like to improve their psychological well-being and life satisfaction. The results suggest that the effect of the intergenerational support exchange should be taken into consideration when improving the quality of life for the elderly.